Monetary policy transmission in Denmark - Rasmus Bisgaard Larsen; Christoffer Jessen Weissert (Danmarks Nationalbank, 2024)
We provide estimates of the transmission of monetary policy shocks from the European Central Bank to Denmark, utilizing high-frequency changes in asset prices during policy announcements that disentangle pure monetary policy shocks from changes in monetary policy related to the European Central Bank's assessment of the economic outlook. Contractionary monetary policy significantly reduces both activity and inflation in Denmark. A one percentage point increase in the three-month money market rate, triggered by a monetary policy shock, roughly results in a one percent drop in prices after one year, an eight percent decline in industrial production after one year and a 1.3 percentage point increase in the unemployment rate after one and a half year. The fall in industrial production translates into a fall in GDP of around four percent. We elaborate on the consumer price response by highlighting two additional findings: a contractionary monetary policy shock leads to i) a significant appreciation of the effective Danish krone rate caused by an appreciation of the euro and ii) a significant drop in tradeable goods prices but an insignificant decline in non-tradeable goods prices. This suggests that the exchange rate response to monetary policy shocks plays an important role in shaping the response of Danish consumer prices to monetary policy shocks.
Keywords: 330; Monetary policy transmission; Research; Danish economy; Economic activity; Economic policy